Uma contribuição para a detecção de faltas fase-terra de alta impedância - Farina, Daniela de Oliveira (2012)
This work deals with the protection of distribution networks of electricity from high-impedance faults (HIF). It proposed a methodology for the detection of HIF by detecting the degree of imbalance of electrical networks and the implementation of the technique in reclosers and switches. It is developed a software to calculate the levels of current imbalance in typical electrical distribution. Thus it was possible to estimate the limits of imbalances typical of unbalanced loads. This made it possible to choose the settings of the detectors imbalances for them to command the opening of the system only when an actual HIF occurs and not when there is an ordinary imbalance. The software was tested in a typical feeder. Finally, it is proposed an outline of the hardware on which the detector imbalance can be implemented.